Moral hazard in a modern federation - Alex Williams (Levy Economics Institute of Bard College, 2020)
The mainstream fiscal federalism literature has led to an instinctive belief that states receiving fiscal aid during a recession are taking advantage of the federal government in pursuit of localized benefits with dispersed costs. This policy brief by Alex Williams challenges this unreflective argument and, in response, offers a novel framework for understanding the relationship between the business cycle and fiscal federalism in the United States. Utilizing the work of Michael Pettis, Williams demonstrates that a government unable to design its own capital structure is not meaningfully an agent with respect to the business cycle. As such, they cannot be considered agents in a moral hazard problem when receiving support from the federal government during a recession. From the perspective of this policy brief, the operative moral hazard problem is one in which federal-level politicians reap a political benefit from a seemingly principled refusal to increase federal spending, while avoiding blame for crisis and austerity at the state and local government level. Williams' proposed solution is to impose macroeconomic discipline on federal policymakers by creating automatic stabilizers that take decisions about the level of state fiscal aid in a recession out of their hands.
Keywords: 330; Coronavirus; Länderhaushalt; Kommunalhaushalt; Finanzausgleich; Moral Hazard; USA